2002
DOI: 10.1002/j.2334-5837.2002.tb02576.x
|View full text |Cite
|
Sign up to set email alerts
|

2.6.4 An Initial Application of AP‐233

Abstract: The System Engineering Design Methodologies (SEDM) project is concerned with potential avenues to exploit the AP-233 system engineering data exchange standard. The project is a joint venture between the System Engineering and Evaluation Centre of the University of South Australia and BAE SYSTEMS Australia. The work described in this paper covers the design and implementation of an import interface from the AP-233 data model to DOORS. The project showed that AP-233 is an effective medium for tool independent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The choice of reasoning strategy impacts profoundly on the other two and is a key decision. Scott and Cook (2002) identified that Case-Based Reasoning (CBR) would be ideally suited to comparing requirements to historically successful requirements and requirements sets. CBR works upon a different technique from other AI systems.…”
Section: Case-based Reasoningmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of reasoning strategy impacts profoundly on the other two and is a key decision. Scott and Cook (2002) identified that Case-Based Reasoning (CBR) would be ideally suited to comparing requirements to historically successful requirements and requirements sets. CBR works upon a different technique from other AI systems.…”
Section: Case-based Reasoningmentioning
confidence: 99%
“…More detail to the model, philosophy and evolution of the AP-233 design can be found in (Johnson, 1999;Johnson et al, 1999;Johnson et al, 2000;Pandikow et al, 2000;Johnson & Herzog, 2001;Herzog & Torne 2001). Scott et al (2002) have shown that AP-233 is well suited as a generic format for holding systems and software requirements and transferring them between dissimilar tools.…”
Section: Ap 233mentioning
confidence: 99%
See 1 more Smart Citation